2017
DOI: 10.1186/s40691-017-0088-y
|View full text |Cite
|
Sign up to set email alerts
|

Cloth(ing) for the dead: case study of three designers’ green burial practices

Abstract: The aim of this study was to explore the current green burial clothing movement by examining three designers’ work using a multi-case study approach. Green burial incorporates a sustainability concept into funeral practices. Cradle-to-cradle, as opposed to cradle-to-grave, is a model for sustainability practices that plan for the product lifecycle to continue after consumer use of the product has concluded. The works of Mark Mitchell, Jae Rhim Lee and Pia Interlandi were selected for the three cases of green b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…When creating goods with a smaller impact on the environment in mind, designers can consider a variety of techniques, strategies materials, creative processes, and methodologies. The slow fashion, longevity design (Connor-Crabb et al, 2016), cradle-to-cradle design (Michel and Lee, 2017), and upgrade recycling and remanufacturing design (Han et al, 2017) are some strategies that have been suggested for designers to use to achieve sustainability. Innovations in products and processes have been created to produce better manufacturing methods that reduce harmful environmental consequences.…”
Section: Koksal Et Al (2017)mentioning
confidence: 99%
“…When creating goods with a smaller impact on the environment in mind, designers can consider a variety of techniques, strategies materials, creative processes, and methodologies. The slow fashion, longevity design (Connor-Crabb et al, 2016), cradle-to-cradle design (Michel and Lee, 2017), and upgrade recycling and remanufacturing design (Han et al, 2017) are some strategies that have been suggested for designers to use to achieve sustainability. Innovations in products and processes have been created to produce better manufacturing methods that reduce harmful environmental consequences.…”
Section: Koksal Et Al (2017)mentioning
confidence: 99%
“…Options include incorporating one's cremated ashes into a nutrient-rich soil for a memorial plant or embedding those ashes into a memorial that will help to regrow coral reefs (https:// livingreefmemorial.com/). Further, you can choose fashionable burial clothing (Michel & Lee, 2017), including a suit that grows mushrooms (Banerji, 2016) or place yourself in a pod that will grow into a tree (https://www.capsulamundi.it/en/). More simply, a body can be buried in an 'ecopod' (https://www.naturalburialcompany.com/ecopod/) or turned into compost (https:// www.recompose.life/) (Barnett, 2018).…”
Section: Green Burialmentioning
confidence: 99%
“…Textiles commercially available for green burials include shrouds and wrappings of natural fibers (Michel & Lee, 2017). Michel and Lee (2017) identified three designers of natural burial garments.…”
mentioning
confidence: 99%